Allelopathic effort of penguin excrements and guanos on the growth of Antarctic soil algae - Akiyama, Masaru; Kanda, Hiroshi; Ohyama, Yoshikuni (1986)
P(論文) An experiment was carried out to ascertain the effect of substances in the soil of Adelie penguin rookery on the growth of algae isolated from the Antarctic soil. In the paper disc test, both of acetone and water extracts of guano soil gave an inhibitive effect on the algal growth. It was recognized that acrylic and oxalic acids were the algal growth inhibitors. The function of the oxalic acid as a new growth inhibitor of algae was examined by comparing it with that of acrylic acid. departmental bulletin paper